SURFACE COMPLEXATION OF PB(II) AT OXIDE-WATER INTERFACES: III. XAFS DETERMINATION OF PB(II) AND PB(II)-CHLORO ADSORPTION COMPLEXES ON GOETHITE AND ALUMINA - IMPLICATIONS FOR ADSORPTION OF METAL IONS IN NATURAL WATERS - Bargar J.R.; Brown G.E.; Parks G.A. (My University, 1998)
Pb(II) sorption on goethite and γ-alumina was studied in aqueous 0.1 M NaCl solutions as a function of pH (5-7), sorption density (1.2-5 μmoles/m2), and [Pb]T (0.24-4.53 mM) using XAFS (X-ray absorption fine structure) spectroscopy. At pH 7, the presence of Cl- has little effect on the Pb(II)/goethite and Pb(II)/γ-alumina adsorbate spectra. However, at pH =< 6, the XAFS spectra indicate the presence of Pb(II)-chloro ternary complexes on goethite. XAFS-derived Pb-Fe distances suggest that these complexes are attached to goethite surfaces through Pb#Osfc and Cl-#Fesfc bonds simultaneously, i.e., both Pb(II) and Cl- ions bond as an inner-sphere species. In contrast, Pb#Cl-#Alsfc ternary complexes were not observed on γ-alumina. These results suggest that the stability trends of Cl-#Me-oxide bonds are similar to the relative stabilities of aqueous Me-chloride complexes, where Me is an oxide-forming cation. Cl-#Fesfc and adsorbate-Cl-#Fesfc bonding should be taken into account when describing surface complexation of Pb(II) and other soft Lewis acid metal ions on iron oxides and iron oxyhydroxides in Cl--bearing waters.